2013
DOI: 10.1200/jco.2013.31.15_suppl.2580
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human trial of novel oral PARP inhibitor BMN 673 in patients with solid tumors.

Abstract: 2580 Background: BMN 673 is the most potent and specific inhibitor of PARP1/2 in clinical development (IC50<1nM). In tumors genetically dependent on DNA repair by homologous recombination PARP inhibition induces synthetic lethality. Methods: Pharmacokinetics (PK), pharmacodynamics (PD), safety and anti-tumor activity of BMN 673 were evaluated in a 2-stage dose-escalation study with 3-6 patients (pts)/dose level. In dose escalation (Stage 1) cycle 1 was 6 wks, with drug taken on days 1 and 8-35, for PK and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…From a tolerability perspective, treatment with PARP inhibitors is commonly associated with dose interruptions, and a smaller proportion of patients require dose reduction and treatment discontinuation. The most common AEs leading to treatment discontinuation include nausea, vomiting, anemia, and thrombocytopenia [5,6,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…From a tolerability perspective, treatment with PARP inhibitors is commonly associated with dose interruptions, and a smaller proportion of patients require dose reduction and treatment discontinuation. The most common AEs leading to treatment discontinuation include nausea, vomiting, anemia, and thrombocytopenia [5,6,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In the TOPARP-A trial, anemia (20%) and fatigue (12%) were the most common grade !3 adverse events; gastrointestinal toxicities were less relevant than reported for ovarian cancer [67]. Hematologic toxicities and fatigue were also the dose-limiting events determining the recommended dose for other PARP inhibitors such as BMN673 and niraparib [54,63].…”
Section: Clinical Development Of Parp Inhibitors In Pcmentioning
confidence: 94%
“…Other PARP inhibitors are in clinical development; data for PC patients are primarily from [ 1 1 _ T D $ D I F F ] gBRCA1/2 mutation carriers with PC who participated in early clinical trials of these compounds. Preclinical studies of BMN673 (Biomarin/ Medivation) demonstrated high potency in inhibiting PARP [62], and tumor responses were seen in BRCA1/2 mutation carriers across tumor types in a phase 1 clinical trial [63]. Rucaparib (AG-014699/CO-338, Pfizer/Clovis Oncology) and veliparib (ABT-888, Abbott Laboratories) have mainly been developed so far in combination with chemotherapies or other targeted agents [64,65].…”
Section: Clinical Development Of Parp Inhibitors In Pcmentioning
confidence: 99%
“…The structures of various PARP inhibitors are shown developed to expand application of PARP inhibitors which show more selectivity towards PARP with more potency and lower toxicity. [41][42][43] GI symptoms, fatigue, anemia 44,45 Veliparib Dizziness, nausea, dysgeusia 35 Nausea, fatigue, lymphopenia 46 Talazoparib Fatigue, nausea, alopecia, anemia, neutropenia, thrombocytopenia 47 Fatigue, alopecia, GI symptoms, anemia, neutropenia, thrombocytopenia 48 Niraparib Anemia, nausea, thrombocytopenia, vomiting, insomnia, constipation, fatigue, anorexia 49 Anemia, thrombocytopenia, neutropenia, GI symptoms, fatigue 49 Rucaparib Fatigue, nausea, diarrhea, vomiting, dizziness, anorexia 50 GI symptoms, fatigue, anaemia 50 azole derivatives as potential dual inhibitors…”
Section: Current Parp Inhibitors In Clinical Trialsmentioning
confidence: 99%